Volumetric Estimation of Lung Dose and Its Association with Pneumonitis Following Radiotherapy in Breast Cancer Patients - Muttath, Geetha; Erakkotan, Greeshma Keloth; Jayaraj, Anjana; Cheruliyil Ayyappan, Suja; Kumar. E.S, Arun; Narayanan, Vinin; Jones, Joneetha; Narendran, Arun. P.; Yahiya, Nabeel; Suresh, Akhil. P.; Malodan, Riyas (Asian Pacific Journal of Cancer Care, 2022)
Introduction: Lung is a major organ at risk during Post Mastectomy RadioTherapy (PMRT), because of the risk of Radiation Pneumonitis (RP). In countries like India 2D RT is widely used due to limited access to advanced technologies. We estimated the lung dose volumetrically in breast cancer patients treated with 2D tangential techniques, the incidence of acute RP and its association with lung dose. Methodology: Retrospective study of patients who underwent PMRT was done. The images with structure sets of cases planned using 2D technique were transferred to TPS and 3 D plans were generated. CLD, MLD, LL were measured from the 2D plan in the CT simulator. LDmean and V20 were measured from from DVH, in the TPS. Correlation between V20 and LDmean was done with CLD, MLD and LL. The incidence of radiation pneumonitis and its association with lung dose also was studied. Result: Total 50 patients were analyzed of which 3 patients had radiation pneumonitis. The mean CLD was 2.28 cm ± 0.54cm, MLD was 2.32 ± 0.6cm and LL was 12.52 ±2cm. V20 for two fields (MT+LT) was 17.04 ± 5.6 Gy and for three field (MT,LT and SCF) was 28.75 ± 8.6 Gy. Positive correlation was found between for V20 & LDmean and CLD, MLD & LL (p<0.05) 6% of patients developed Radiation pneumonitis but did not have association with V20 or MLD. Conclusion: Radiation pneumonitis is major concern after chest wall irradiation and the incidence is expected to be high with conventional technique where the volume is not accurately measured. It is still an option in countries like India with resource constraints by planning cautiously with the indicators of irradiated lung, like CLD and MLD within limits thus minimizing the incidence of radiation induced lung injury.